S115. NOVEL TECHNIQUES FOR THERAPEUTIC DRUG MONITORING FOR CLOZAPINE LEVELS. (9th April 2019) - Vyas, Gopal; Buckley, Tiffany; Kitchen, Christopher; Siegfried, Nathan; Tefera, Eshetu; Chen, Shou; DiPaula, Bethany; Kelly, Deanna
Abstract: Background: Clozapine is an effective antipsychotic for treatment-resistant schizophrenia for which serum levels could guide therapy decisions. It is underutilized because it requires venous draws and several-day determination time with high performance liquid chromatography-tandem mass spectrometry (LC/MS-MS). This project evaluates if clozapine measured with a novel immunoassay technology, which could be developed into a fingerstick test, correlate with LC/MS-MS. This project also assesses the impact of demographic and clinical variables on assay results. Methods: 117 serum samples (N=48 with schizophrenia on clozapine, N=24 with schizophrenia not on clozapine and N=45 healthy controls) were included. One aliquot was sent to a national reference laboratory (NRL) for determination by LC/MS-MS and another sent to Saladax for immunoassay (MyCare® Psychiatry Clozapine Assay Kit). The agreement was compared using Concordance Correlation Coefficient (CCC). Participants' age, sex, race-ethnicity, smoking status, ascorbic acid, co-medications and complete metabolic panel were collected. Linear regression and mixed model were performed for both technologies correspondingly to examine the impact of these variables. Results: Clozapine levels by the NRL had 19 false positive readings (mean 48.8 ± 14.3, range 21–138 ng/ml) in schizophrenia participants not on clozapine (N=3) and healthy controls (N=16). The immunoassay had no false positive results. A mixed effects model (with a time average of the NRL and 3 immunoassay runs), yielded a strong Pearson correlation (r=0.843, p <0.0001). The mean clozapine level was 414.98 ng/ml on the LC/MS-MS and 472 ng/ml on the immunoassay. Although immunoassay was significantly higher than the LC/MS-MS measurement (p=0.013), the agreement level was high (CCC=0.76; 95% CI 0.64, 0.84). No association was found between age, sex, smoking status, albumin, globulin, and ascorbic acid on clozapine levels; however, African-Americans (AA) had clozapine levels 113.4 ng/ml higher (standard error (SE): 55.18, p=0.045) than non-AA by LC/MS-MS and 190.8 ng/ml (SE: 80.76, p=0.022) higher by immunoassay. Additionally, total protein was related to clozapine levels (LC/MS-MS p=0.046, immunoassay p=0.046). For each unit increase in total protein an increase of 145.6 units (SE: 70.81) was predicted for LC/MS-MS and a 225.5-unit (SE: 104.60) increase for the immunoassay. Discussion: Immunoassay results were in good agreement with LC/MS-MS results in clozapine-containing samples, indicating good assay performance. The lack of false positives in the immunoassay results may indicate higher specificity than LC/MS-MS methods. Total protein values may lead to changes in clozapine values. More work is needed to account for total protein values when decision-making with clozapine results. This was funded in part by NIMH R56 (MH105571-02) and NIMH R01 (MH102215). Saladax provided funding for the immunoassay (MyCare® Psychiatry Clozapine Assay Kit*) results.*CE/RUO in US